Kelley's textbook of rheumatology - Firestein, Gary S.; Budd, Ralph C.; Gabriel, Sherine E.; McInnes, Iain B.; O'Dell, James R. (Elsevier/Saunders, 2013)
Helps you to better understand scientific underpinnings of rheumatic diseases, so that you can better manage your patients